Evaluation on Economic Benefits of Adoption of High-quality Rice Cultivars - A Study Based on Survey Data from Rice Farmers in Guangdong Province - Shuting YANG; Zedong YAN; Fengbo CHEN (Guangdong nongye kexue)
【Objective】With the increasing demand for high-quality rice in the market, a scientific evaluation on the grain planting benefits of high-quality rice and ordinary-quality rice is of vital significance to increase farmers income and steer future directions in rice breeding.【Method】Based on the survey data from rice farmers in Guangdong Province during 2021- 2022, the endogenous switching regression model was used to evaluate the planting benefits associated with high-quality and ordinary-quality rice. Furthermore, it conducted an analysis on the grain planting benefits with respect to different planting seasons (early rice and semi-late rice).【Result】In terms of yield, high-quality rice had a lower yield compared with ordinary rice. Specifically, the yields of high-quality rice decreased by 10.34% and 0.27% compared with ordinary rice in different plots. This indicated that, while maintaining its quality advantage, high-quality rice may require a sacrifice in yield. In terms of planting costs, high-quality rice did not have an absolute cost advantage compared with ordinary rice. In high-quality rice plots and ordinary rice plots, the planting costs of high-quality rice increased by 0.93% and decreased by 7.62%, respectively, compared with ordinary rice. This result suggested that the planting cost of high-quality rice was greatly influenced by plot characteristics and it showed significant variation across different plots. In terms of net income, the net income from planting high-quality rice was higher than that from ordinary rice. The net income from planting high-quality rice in high-quality rice plots increased by 4.69% compared with that from ordinary rice, while in ordinary rice plots, the increase reached 45.44%. This indicated that although high-quality rice had certain disadvantages in yield, its higher market value showed better net income performance compared with ordinary rice.【Conclusion】In the context of backdrop of rice production increasingly influenced by market factors, the area dedicated to high-quality rice is showing an overall expansion trend, which improves the rice planting benefits to some extent but may also introduce the risk of reduced grain output. Balancing quality with moderate high yields should be an important direction for rice breeding in the future.